2000
DOI: 10.1085/jgp.116.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Severed Molecules Functionally Define the Boundaries of the Cystic Fibrosis Transmembrane Conductance Regulator's Nh2-Terminal Nucleotide Binding Domain

Abstract: The cystic fibrosis transmembrane conductance regulator is a Cl− channel that belongs to the family of ATP-binding cassette proteins. The CFTR polypeptide comprises two transmembrane domains, two nucleotide binding domains (NBD1 and NBD2), and a regulatory (R) domain. Gating of the channel is controlled by kinase-mediated phosphorylation of the R domain and by ATP binding, and, likely, hydrolysis at the NBDs. Exon 13 of the CFTR gene encodes amino acids (aa's) 590–830, which were originally ascribed to the R d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
122
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 47 publications
13
122
0
Order By: Relevance
“…to increase channel closing rate). A role for the N-tail in modulating channel opening rate is also supported by the recent findings of Chan et al (15), who reported that CFTR channels that had been epitope-tagged at the amino terminus exhibited reduced opening rates in excised patches. Our prior failure to detect an obvious effect of the alanine and cysteine substitutions on channel opening rate may be due to the fact that absolute rates of channel opening can be overestimated in multichannel patches that contain mutant channels with low activity (i.e.…”
Section: Covalent Modification Of the Double Cysteine Mutant Alters Amentioning
confidence: 55%
See 2 more Smart Citations
“…to increase channel closing rate). A role for the N-tail in modulating channel opening rate is also supported by the recent findings of Chan et al (15), who reported that CFTR channels that had been epitope-tagged at the amino terminus exhibited reduced opening rates in excised patches. Our prior failure to detect an obvious effect of the alanine and cysteine substitutions on channel opening rate may be due to the fact that absolute rates of channel opening can be overestimated in multichannel patches that contain mutant channels with low activity (i.e.…”
Section: Covalent Modification Of the Double Cysteine Mutant Alters Amentioning
confidence: 55%
“…We observed previously that the isolated N-tail could bind in vitro to a peptide fragment of CFTR (residues 595-813) that included the distal portion of NBD1 followed by the R domain (13). (At the time of that study residues 595-813 were thought to constitute the R domain alone (4); however, the more recent functional data of Chan et al (15) indicate that NBD1 probably extends to between residues 622 and 634.) N-tail mutations that disrupt binding to this NBD1/R domain fragment have no effect on channel phosphorylation (14), but it is possible that R domain phosphorylation could be affected by chemical modification of these sites.…”
Section: Covalent Modification Of the Double Cysteine Mutant Alters Amentioning
confidence: 99%
See 1 more Smart Citation
“…2). As noted these boundaries were previously functionally designated by Chan and co-workers (17). As the Western blots in Fig.…”
Section: B Lane 10 C Lane 10)mentioning
confidence: 64%
“…Calnexin may facilitate CFTR folding by stabilizing MSD2 and thereby promoting formation of proper contacts between MSD1 and MSD2. To test this model, we took advantage of the observation that split CFTR fragments that individually contain the N-and C-terminal subdomains assemble into an ion channel when expressed in trans (Chan et al, 2000). Nterminal CFTR fragments containing MSD1, NBD1, and the R domain fold to a conformation that has a long half-life and accumulates at high levels when expressed alone or in trans with CFTR 837-1480 (Ostedgaard et al, 1997;Xiong et al, 1997;Meacham et al, 1999).…”
Section: Calnexin Promotes Interactions Between Msd1 and Msd2 Of Cftrmentioning
confidence: 99%